(3oeNJUQ GdGfJUGa ef GdcTGas - (3Yde GdOjf YHO GdcQje Hf Ydj GdYQGbjs; (3CMeO Hf eMeO Hf Ydj GdGScfOQj, GHf GdefjQs ((3eMeO Hf eMeO HQj s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeg Yde GdOjf GdYQGbj bO GNJUQJ aj gPG GdcJGH GdEfJUGa ef GdcTGa s
(3BNQgG (B:s
(3gPG BNQ cJGH oeNJUQ GdEfJUGa Ydi GdcTGa hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1477s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs